Saliva as a Diagnostic Biopsy Fluid: A Review - Alarcón-Sánchez, Mario Alberto; Lomelí-Martínez, Sarah Monserrat; Mudasser, Muhammad Adeel; Escoto-Vasquez, Lilibeth-Stephania; Becerra-Ruiz, Julieta Sarai; Rivera-Solano, Rolando; Khurshid, Zohaib; Heboyan, Artak (European Journal of General Dentistry, 2025)
Saliva is a biofluid secreted mainly by the major and minor salivary glands, which contains a wide variety of biomolecules with diagnostic value. Its molecular abundance, noninvasive collection, molecular richness, and link to systemic conditions have established it as an attractive tool compared with blood or tissue biopsies. The present narrative review aims to integrate up-to-date knowledge about the biology of the salivary glands, the mechanisms of secretion, and the molecular constitution of this biofluid; at the same time, it analyzes its role in oral and systemic health. It highlights advances in salivaomics and its diagnostic role in oral, systemic, metabolic, oncological, autoimmune, and neurodegenerative pathologies. Additionally, it analyzes the impact of prosthetic biomaterials on both salivary composition and the expression of inflammatory markers. Finally, it recognizes the challenges related to biological variability, the need for standardization and validation of biomarkers, highlighting the potential of integrating multi-omic platforms and artificial intelligence to promote a promising path for diagnostic precision in dentistry and medicine.
Keywords: saliva biomarkers; salivary diagnostics; prosthetic biomaterials; oral disease; salivaomics